2021
DOI: 10.3389/fendo.2021.771575
|View full text |Cite
|
Sign up to set email alerts
|

Intersections in Neuropsychiatric and Metabolic Disorders: Possible Role of TRPA1 Channels

Abstract: Neuropsychiatric disorders (NPDs) are a huge burden to the patient, their family, and society. NPDs have been greatly associated with cardio-metabolic comorbidities such as obesity, type-2 diabetes mellitus, dysglycaemia, insulin resistance, dyslipidemia, atherosclerosis, and other cardiovascular disorders. Antipsychotics, which are frontline drugs in the treatment of schizophrenia and off-label use in other NPDs, also add to this burden by causing severe metabolic perturbations. Despite decades of research, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 111 publications
1
3
0
Order By: Relevance
“…We have previously shown that this model correlated with our therapeutic outcomes in both clinical trials of AD and the MC903 mouse model [16]. Activation with the TRPA1 agonist cinnamaldehyde [24] reduced modeled healing in both the HaCaT keratinocyte (KC) and Schwann (neuronal) cell lines (Fig 5E and 5F). Blockade of TRPA1 improved healing times in Schwann cells but not in KC (Fig 5E and 5F).…”
Section: Trpa1 Effect On Wound Cultures Are Modulated By Catecholamin...supporting
confidence: 61%
“…We have previously shown that this model correlated with our therapeutic outcomes in both clinical trials of AD and the MC903 mouse model [16]. Activation with the TRPA1 agonist cinnamaldehyde [24] reduced modeled healing in both the HaCaT keratinocyte (KC) and Schwann (neuronal) cell lines (Fig 5E and 5F). Blockade of TRPA1 improved healing times in Schwann cells but not in KC (Fig 5E and 5F).…”
Section: Trpa1 Effect On Wound Cultures Are Modulated By Catecholamin...supporting
confidence: 61%
“…TRPA1, positioned strategically in epithelial cells throughout the gastrointestinal tract, plays a pivotal role in sensory transduction of dietary components. Its responsiveness to a diverse array of chemicals, including those found in spicy foods (e.g., isothiocyanates) ( Wu et al, 2017 ; Radhakrishnan et al, 2023 ) and pungent substances (e.g., allicin in garlic) ( Sodhi et al, 2021 ), underscores its significance in translating the chemical landscape of ingested nutrients into cellular signals. Considering its physiological function in the gastrointestinal tract, TRPA1 agonists, such as allicin and AITC, might exert a regulatory influence on gastrointestinal motility ( Tsuchiya and Kawamata, 2019 ).…”
Section: Trpa1 In the Gastrointestinal Tractmentioning
confidence: 99%
“…Agonists and antagonists targeting TRPA1 have demonstrated effectiveness in treating neuropsychiatric disorders and appetite regulation, establishing a vital connection between the two. TRPA1 channels play a role in regulating appetite, lipid metabolism, glucose and insulin homeostasis, and the inflammation associated with neuropsychiatric and metabolic disorders ( Sodhi et al, 2021 ). Non-electrophilic TRPA1 activators, including menthol, carvacrol, and clotrimazole, induce an increase in the permeability of fluorescein isothiocyanate-conjugated dextran (4 kDa) and a decrease in transepithelial electrical resistance in epithelial MDCK II monolayers.…”
Section: Trpa1 In the Gastrointestinal Tractmentioning
confidence: 99%
“…These channels are reported to be stimulated by a wide range of irritants namely allyl isothiocyanate, allicin, and cinnamaldehyde. 64 , 65 Furthermore, an array of endogenous molecules released during inflammation and oxidative stress have been found to be involved in TRPA1 activation, evidently highlighting a potential role of this channel in pain and nociception. A growing body of evidence employing animal models suggests the therapeutic potency of TRPA1 antagonists namely HC-030031, A-967079, and AMG0902 in human subjects undergoing neuropathic pain.…”
Section: Trpa1 As a Drug Targetmentioning
confidence: 99%